18F-fluciclovine PET Imaging of Non-PSMA Expressing High-risk Primary Prostate Cancer - Ismaheel O. Lawal; Lara R. Harik; Akshay S. Bedmutha; Sagar A. Patel; Ashesh B. Jani; David M. Schuster (Clinical Nuclear Medicine, 2026)
A 67-year-old man with rising PSA and palpable prostate lesion underwent prostate MRI, which showed a large PI-RADS 5 lesion confirmed on biopsy as Gleason score 9 (4+5), grade group 5, prostate cancer. 18 F-DCFPyL PET/CT scan for initial stage showed no significant PSMA avidity in the prostate lesion. 18 F-fluciclovine was obtained for off-label disease staging and management guidance. The high Gleason score prostate lesion showed intense 18 F-fluciclovine avidity. High expression of amino acid transporters and low PSMA expression was confirmed by immunohistochemistry. This case showcases a non-PSMA-avid primary prostate cancer with intense 18 F-fluciclovine, demonstrating the potential of 18 F-fluciclovine PET/CT as an off-label alternative in the uncommon primary prostate cancer without significant PSMA expression.